PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 13 BANTAN TUA - Risnawati, Risnawati; Noviana, Eddy; Syahrilfuddin, Syahrifuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to find out whether the implementation cooperative learning model mind mapping can improve social science learning results of Class IV Students in SD Negeri 13 Bantan Tua. The type of this research is classroom action research (CAR) with the research subjects are class IV Students which amount to 20 students. The data collection techniques. Used is observation and tests. The research concluded that social science learning which using cooperative learning model mind mapping can improve the teacher’s activity, student’s activity and social science learning result. At the first meeting of cycle I, the teachers’s activity percentage was 70,83% and categorized good, at the second meeting the percentage increased to be 83,33% and categorized good. For cycle II at the first meeting the percentage was 91,66 % and categorized very good, at the second meeting increased to be 95,83% and categorized very good. Then for studen’s activity cycle I at the first meeting the percentage was 75% and categorized good, inthe second meeting the percentage was 79,16% and categorized good. For the first meeting of cycle II the percentage was 83,33 % and categorized very good, at the second meeting the percentage was 91,66% and categorized very good. The student’s social science learning result from the average grades before actions (basic score) was 59,3 decline at cycle I to be 64,5 with the percentage by5,2% and at cycle II the average grades increased to be 70,25 with the percentage increase by 10,95% from the basic score by 59,3/Keywords: Cooperatif learnin gmodel Mind Mapping,Type,social science learning Result.